2016
DOI: 10.1021/acs.jpcb.6b06423
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Dynamics of Zwitterionic Micelles and Their Hydration Waters by Gigahertz-to-Terahertz Dielectric Spectroscopy

Abstract: Gigahertz-to-terahertz spectroscopy of macromolecules in aqueous environments provides an important approach for identifying their global and transient molecular structures, as well as directly assessing hydrogen-bonding. We report dielectric properties of zwitterionic dodecylphosphocholine (DPC) micelles in aqueous solutions over a wide frequency range, from 50 MHz to 1.12 THz. The dielectric relaxation spectra reveal different polarization mechanisms at the molecular level, reflecting the complexity of DPC m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 72 publications
4
45
0
Order By: Relevance
“…It was argued that the experimental relaxation time reflects the average dynamics of water molecules in the micelles. These assignments are in consistent with the more recent results from experiments . It is presumed that changes observed in the relaxation time of hydration water for the two surfactants are due to the different level of hydration of micelles.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It was argued that the experimental relaxation time reflects the average dynamics of water molecules in the micelles. These assignments are in consistent with the more recent results from experiments . It is presumed that changes observed in the relaxation time of hydration water for the two surfactants are due to the different level of hydration of micelles.…”
Section: Resultssupporting
confidence: 91%
“…Lanzi et al attributed the relaxation time of 120 ps for SDS to the interfacial bound water. Deepu K. George et al observed the cooperative molecular dynamics in hydrated layers of DPC micelles. Baar et al assigned the relaxation time τ = 25 ps to the water molecules surrounding the hydrophobic chain.…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric relaxation of aqueous NaCl solutions without surfactant in a frequency range from 20 MHz to 40 GHz features only one relaxation peak . This is different for the samples containing surfactants but no NaCl where up to four different relaxation processes are reported in this frequency range .…”
Section: Resultsmentioning
confidence: 82%
“…That is, the tangential micellar and the water molecules hydrogen bond relaxations. As mentioned in the Section Introduction, there is another relaxation process for aqueous surfactant solutions with a relaxation time of about 100 ps (i=3) reported in the literature . However, all of our attempts to incorporate this relaxation process in our regression analysis result in a diminished degree of the coefficient of determination of the fitted parameters.…”
Section: Theorymentioning
confidence: 86%
See 1 more Smart Citation